2017
DOI: 10.1158/1078-0432.ccr-16-3066
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-oncology Clinical Trial Design: Limitations, Challenges, and Opportunities

Abstract: Recent advances in immuno-oncology and regulatory approvals have been rapid and paradigm shifting in many difficult-to-treat malignancies. Despite immune checkpoint inhibitor therapy becoming the standard of care across multiple tumor types, there are many unanswered questions that need to be addressed before this therapeutic modality can be fully harnessed. Areas of limitations include treatment of patients not sufficiently represented in clinical trials, uncertainty of the optimal treatment dosing and durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 63 publications
1
40
0
Order By: Relevance
“…For instance, the optimum, cost-effective doses have not been determined for many approved immune checkpoint inhibitors. 53 Although flat dosing is feasible for immune checkpoint inhibitors because there is no clear relationship between dose response or dose toxicity, weight-based doses continue to be approved for some. While treatment with ipilimumab is usually limited to 4 doses, the optimal treatment duration for other immune checkpoint inhibitors is not defined.…”
Section: Optimizing Schedules For Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the optimum, cost-effective doses have not been determined for many approved immune checkpoint inhibitors. 53 Although flat dosing is feasible for immune checkpoint inhibitors because there is no clear relationship between dose response or dose toxicity, weight-based doses continue to be approved for some. While treatment with ipilimumab is usually limited to 4 doses, the optimal treatment duration for other immune checkpoint inhibitors is not defined.…”
Section: Optimizing Schedules For Cancer Therapymentioning
confidence: 99%
“…Table 6 outlines some strategies to increase clinical trial efficiency. 53,74,79,[81][82][83][84][85][86][87][88][89] An international body representing the governments of all countries and working in partnership with academic research groups, cancer clinical trial networks (eg, the National Cancer Institute, the Institute of Cancer Research, the European Society for Medical Oncology, the American Society of Clinical Oncology), the World Health Organization, the pharmaceutical industry, not-for-profit organizations, and patient advocate groups could be responsible for setting the global research priorities for developing cancer medicines. It is not a responsibility that should be fragmented or left to one sector alone.…”
Section: Optimizing Cancer Medicine Researchmentioning
confidence: 99%
“…In fact, Baik et al reported the limitations, challenges and opportunities in the immuno‐oncology clinical trial design. They found that due to the rapidity of development, competition, and race for FDA approval, the optimal dosing and schedule of ICIs are still not fully defined and continue to be under study …”
Section: Proof‐of‐principle Of Low‐dose Ici Therapy Has Been Demonstrmentioning
confidence: 99%
“…They found that due to the rapidity of development, competition, and race for FDA approval, the optimal dosing and schedule of ICIs are still not fully defined and continue to be under study. 85 Importantly, Kleef's protocol consists only of approved drugs and treatments. Therefore, our prediction that low-dose ICI-induced autoimmune T cells are powerful therapeutic tools can be confirmed or refuted in prospective, controlled clinical trials.…”
Section: Low-dose Ici Therapy Has Been Demonstrated In 111 Single Casmentioning
confidence: 99%
“…In addition, many early phase immunotherapy studies have not requested or mandated these biopsies, a potential shortcoming. In part due to the restricitive nature of clinical trial eligibility (55), many patients who must receive immunotherapy as standard of care may have limited opportunities to participate in research directed at studies of resistance, as such studies may be infrequent or under-resourced. A creative solution to this has been the efforts of patient advocacy groups to begin international tissue bank consortia, for instance in melanoma (56).…”
Section: The Search For Valuable Immuno-oncology Biomarkers Requires mentioning
confidence: 99%